Factors associated with early cessation of breastfeeding in women with gestational diabetes mellitus. Issue 2 (June 2015) - Morrison, M.K.; Collins, C.E.; Lowe, J.M.; Giglia, R.C.
Abstract Aim To determine factors associated with early cessation of breastfeeding (≤3 months) in women with recent gestational diabetes mellitus (GDM). Methods A cross-sectional online survey of women aged ≥18 years, diagnosed with GDM in 2010 and registered with the National Diabetes Services Scheme in Australia. The 59 questions examined breastfeeding duration, intention, attitudes, exclusivity and support. Results 738 women completed the survey (15% response rate). Data was analysed for 729 eligible respondents. Of these 97% reported 'ever' breastfeeding and 19% had breastfed for ≤3 months. Cessation of breastfeeding at or before 3 months was associated with breastfeeding problems at home [adjusted odds ratio 8.01, 95% confidence interval (4.57, 14.05)], return to work prior to three months [OR 3.39 (95% CI 1.53, 7.55)], inadequate breastfeeding support [OR 1.88 (95% CI 1.10, 3.22)], caesarean delivery [OR 1.70 (95% CI 1.04, 2.76)], low socioeconomic status (SEIFA 1 unit increase) [OR 0.89 (95% CI 0.81, 0.97)] and BMI (2 unit increase) [OR 1.08 (95% CI 1.01, 1.57)]. Being married or de facto [OR 0.14 (95% CI 0.03, 0.62)] was a protective against early cessation of breastfeeding. Conclusion Strategies to improve breastfeeding duration in women with GDM need to address those most at risk of early cessation and provide appropriate postpartum breastfeeding support in this group.